Silent knit, deadly knit - Ehrhart, Peggy (Ehrhart, Peggy. Knit & Nibble mystery., 2019)
Pamela has been in merry spirits since her artsy daughter Penny returned home from college for the holidays. But their mother-daughter bonding time gets cut short when a terrified Penny stumbles upon the dumped body of Millicent Farthingale, a wealthy craft shop owner who was popular for all the wrong reasons. From a scheming business partner to a seedy husband several years her junior, Millicent attracted scammers so in love with her assets, they<U+2019>d toss her down a chimney to get their paws on them. Now, with only a hand-knit red scarf connecting the killer to the crime, Pamela and the Knit and Nibblers could use some extra creativity as they find out who<U+2019>s really naughty or nice in Arborville<U+2014>because going up against a looming culprit is DIY or die!